Evaluation of 5G Modulation Candidates WCP-COQAM, GFDM-OQAM, and FBMC-OQAM in Low-Band Highly Dispersive Wireless Channels - Lizeaga, Aitor; Rodríguez, Pedro M.; Val, Iñaki; Mendicute, Mikel (Journal of Computer Networks and Communications, 2017)
We analyse some of the candidates for modulations for 5G: FBMC-OQAM, GFDM-OQAM, and WCP-COQAM. Unlike most of the related bibliographies, which are oriented to mobile communications, our research is focused on 5G in cognitive radio based industrial wireless communications. According to the ultrareliability and low-latency requirements of industrial communications, we simulate the aforementioned modulations in low-band transmissions (carrier frequencies below 6 GHz and a bandwidth narrower than 100 MHz) through large indoor spaces and severe multipath channels that emulate industrial halls. Moreover, we give detailed information about WCP-COQAM and how the windowing affects the protection against multipath effect and reduces spectral efficiency compared to GFDM-OQAM. We also compare the aforementioned filtered multicarrier techniques and OFDM in terms of robustness against multipath channels, power spectral density, and spectral efficiency. Based on these results, we aim at providing an approximate idea about the suitability of 5G MCM candidates for industrial wireless communications based on CR.